Implementasi ISAK 35 pada Lembaga Perkreditan Desa - I Nyoman Darmayasa; I Ketut Parnata; Ni Luh Putri Setyastrini (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to design the format of the LPD financial statements referring to the Interpretation of Financial Accounting Standards (ISAK) 35 in accordance with the characteristics of the LPD.Method: The research method used is Participatory Action Research (PAR) combined with Local Genius Values (LGV). The data comes from the experience and knowledge of researchers on LPD bookkeeping assistance in 2022.Results: The results of the design of the bookkeeping format refer to SAK ETAP terminology which is non-profit oriented according to ISAK 35 based on the locality values of the Balinese indigenous people. The design of this bookkeeping format strengthens the characteristics of the LPD as an institution owned by indigenous peoples which is not a tax subject. The design of this bookkeeping format is expected to be an alternative consideration for various stakeholders to formulate standardized financial reporting policies for all LPDs that remain rooted in the local value characteristics of the Balinese indigenous people.Implications: This study presents the new design of the bookkeeping format for LPDs in refer to Interpretation of Financial Accounting Standards (ISAK) 35 and the characteristics of LPD.Novelty: This study has a novelty related to the design of the bookkeeping format for LPD in refer to Interpretation of Financial Accounting Standards (ISAK) 35.Â